Mediation effects of thyroid function in the associations between phthalate exposure and lipid metabolism in adults - Han-Bin Huang; Po-Keng Cheng; Chi-Ying Siao; Yuan-Ting C. Lo; Wei-Chun Chou; Po-Chin Huang (BMC, 2022)
Abstract Phthalates are a group of industrial chemicals widely used in everyday products including cosmetics, food packaging and containers, plastics, and building materials. Previous studies have indicated that urinary phthalate metabolites are associated with metabolic effects including those on lipid metabolism, but the results are mixed. Furthermore, whether thyroid function mediates the association between phthalate exposure and lipid metabolism remains unclear. In the present study, we explored whether changes in thyroid function markers mediate the associations between phthalate exposure and lipid metabolism indicators in Taiwanese adults. The cross-sectional data were obtained from the Taiwan Environmental Survey for Toxicants conducted in 2013. Levels of 11 urinary phthalate metabolites, levels of 5 thyroid hormones, and 8 indicators of lipid metabolism were assessed in 222 Taiwanese adults. The relationships of urinary phthalate metabolite levels with serum thyroid hormone levels and lipid metabolism indicators were explored using multiple regression models. Mediation analysis was conducted to evaluate the role of thyroid function in the association between phthalate exposure and lipid metabolism. The metabolite of di(− 2-ethylhexyl) phthalate (∑DEHPm) exhibited a significant positive association with the lipid metabolite indicator of high-density lipoprotein cholesterol (HDL-C; β = 0.059, 95% confidence interval [CI] = 0.009, 0.109) in adults, and the thyroid function indicator thyroxine (T4) had a significant negative association with the metabolite ∑DEHPm (β = − 0.059, 95% CI = − 0.101, − 0.016) and a significant negative association with HDL-C (β = − 0.284, 95% CI = − 0.440, − 0.128). The T4 indirect effect was 0.015 (95% CI = − 0.0087, 0.05), and the mediation effect was 32.2%. Our results support the assumption that exposure to phthalates influences the homeostasis of lipid metabolism by interfering with thyroid function.